Pengaruh Perceived Price, Brand Experience Dan Merchandising Visual Terhadap Keputusan Pembelian Pada Toko Sardo Malang (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Muchyidin, Yahya; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract These research is designed to investigate impact of Perceived Price, Label Experience, plus Visual Design towards purchasing decisions at Sardo Store Malang, with a case study involving students of the Islamic University of Malang. The study adopts a quantitative explanatory approach and employs multiple linear regression analysis. A total of 75 respondents were selected using the Malhotra formula. Data were analyzed with SPSS version 25, including tests for validity, reliability, normality, classical assumptions, hypotheses, and the coefficient of determination (R²). The results reveal that the three independent variables jointly exert a significant influence on consumer purchasing decisions at Sardo Store Malang. More specifically, Perceived Price and Brand Experience show a positive effect on purchasing decisions, whereas Visual Design does not exhibit a significant effect. Keywords: Perceived Price, Brand Experience, Visual Design, Purchasing Decisions.